FAKTOR-FAKTOR YANG MEMPENGARUHI POLA ASUH GIZI PADA BALITA BGM DI KECAMATAN MUMBULSARI KABUPATEN JEMBER - Trisna Pangestuning Tyas (Jurnal Kesehatan dr. Soebandi, 2013)
Nutritional status can be influenced by nutrition parenting practices performed in the household are realized with the availability of food and medical care and other resources for survival, growth and development of children. Nutrient deficiency in infancy and child - a child can lead to state of the BGM (Lower Red Line). The research objective was to determine factors - factors that influence parenting nutrition in children with BGM at Mumbulsari district Jember. The study design was observational analytic. Population of 56 mothers who have BGM children in District Mumbulsari Jember.Sampel of 56 mothers who have BGm children. Collecting data using questionnaires and KMS. Data were tabulated and presented in picture, also Ordinal Regression statistical tests. Results showed most respondents have less nutrition parenting is 29 respondents (52%). Based on Ordinal Regression statistical test results obtained on the variable P value of Age (0.398), Education (0.650), Employment (0.460) and parity (0.710), which means P>a or Ho received. So there is no effect between age, education, employment, and parity with parenting nutrition. The conclusion is Age, Education, Employment, and Parity is not affecting Parenting Nutrition. Suggestions for improving nutritional quality of cares patern of nutritions is to giving love and care to the children also provide information about the nutrition issues by under 5th years old children.